No Effect of Added Sugars in Soft Drink Compared With Sugars in Fruit on Cardiometabolic Risk Factors: Results From a 4-Week, Randomized Controlled Trial - Te Morenga, Lisa; Mallard, Simonette R.; Ormerod, Fabiane B. (Frontiers in Nutrition, 2021)
High intakes of added sugar from soft drinks are associated with negative health outcomes such as the increased risk of gout and type 2 diabetes, weight gain and cardiovascular disease. Fruits are naturally high in sugars but their effect on cardiometabolic risk remains unknown. We examined the effect on cardiometabolic risk factors of consuming natural sugars from fruit or added sugars from sugar-sweetened soft drinks in overweight adults. 48 healthy, overweight (BMI≥ 28 kg/m2) men (n = 21) and women (n = 20) were randomised to either a fruit (n = 19) or sugar-sweetened soft drink (n = 22) intervention for 4 weeks. The fruit group received 6 items of fresh and dried fruit per day and the sugar-sweetened soft drink group received 955ml of sugar-sweetened soft drink per day. The interventions were matched for both energy (fruit: 1800 kJ/d; soft drink: 1767 kJ/d) and fructose content (fruit: 51.8 g/d; soft drink: 51.7 g/d). The soft drink intervention provided 101g total sugars, which was all added sugar and the fruit intervention provided 97g total sugars, which were all natural sugars. Dietary intakes were otherwise ad libitum. Despite being asked to consume additional sugar (up to 1800 additional kJ/d) , there were no changes in weight, blood pressure or other cardiometabolic risk factors, except by uric acid, in any of the intervention groups. In conclusion, our findings do not provide any evidence that short-term regular intake of added sugars is linked to higher cardiometabolic risks, with exception of uric acid in overweight men. Public health interventions to prevent obesity and related diseases should focus on the quality of the whole diet rather than only focusing on reducing sugary drinks or sugar intakes.